Development of a novel dengue virus serotype-specific multiplex real-time reverse transcription-polymerase chain reaction assay for blood screening - Tezuka, Kenta; Kuramitsu, Madoka; Okuma, Kazu; Nojima, Kiyoko; Araki, Kumiko; Shinohara, Naoya; Matsumoto, Chieko; Satake, Masahiro; Takasaki, Tomohiko; Saijo, Masayuki; Kurane, Ichiro; Hamaguchi, Isao (Transfusion (Philadelphia, Pa.), 2016)
BACKGROUND Dengue fever is caused by four related RNA viruses of the genus Flavivirus, dengue virus (DENV)‐1, ‐2, ‐3, and ‐4, which are transmitted to humans by mosquitoes. Although DENV is not endemic in Japan, an autochthonous dengue outbreak occurred in 2014. Several transfusion‐transmitted cases have also been reported after the use of blood and plasma products in DENV‐endemic countries. The aim of this study was to develop a novel multiplex reverse transcription–polymerase chain reaction (RT‐PCR) assay for DENV blood screening. STUDY DESIGN AND METHODS Large‐scale oligonucleotide screening was performed to obtain DENV‐specific primers and probes using a variety of DENV clinical isolates. A multiplex RT‐PCR assay was then developed using the identified oligonucleotides and the ability of this assay to detect DENV RNA was evaluated. RESULTS A number of oligonucleotides suitable for DENV RNA detection were identified and a novel DENV serotype‐specific multiplex RT‐PCR assay was successfully established. Comparative analysis revealed that the multiplex assay could detect levels of viral contamination as low as 100 viral copies/mL. CONCLUSION This established serotype‐specific multiplex RT‐PCR assay provides a simple, sensitive, and quantitative detection method for DENV, which could be applied in the screening of blood samples to prevent transfusion‐transmitted DENV infection.